O anarquismo no movimento punk: cidade de São Paulo (1980-1990) - Oliveira, Valdir da Silva (2007)
The present work comes from my experiences and concerns with the decade of the 1980 s. When living at Parque São Rafael, a district located on the east side of São Paulo city, I had the opportunity to witness the punk movement that grew in the city. Nevertheless, what really called my attention was the little, but growing, commitment to the punk movement with anarchist ideas which were expressed by its practices and experiences. The main aim of this reasearch is to analyse, discusss and study the anarchism in the punk movement, taking into account its political, social and cultural characteristics in São Paulo city. In order to analyse it, the study is based on documents, texts, enterviews, letters, articles and fanzines published by punk members of the studied historical period. We tried to give voice and visibility to historical individuals which actively integrated the punk movement and had relation to anarchist ideas in the decade of the 1980 s. We also bared in mind that the punks are social individuals living and interacting in society. It is known that those interactions are marked by struggles, resistance and interference in their search for indentity references in the city. So our intention is to make a contribuition to the debate and discussion about anarchism in the punk movement. This study does not include conclusions but discusses the ways and interactions in the punk movement related to anarchism as they aimed at an anarchist society. That attitude is still alive in many groups called anarcho-punks which continue their protests in São Paulo